Framework for resilience strategies in agricultural supply chain: assessment in the era of climate change - Yuan, Minqian; Hu, Haiqing; Xue, Meng; Li, Jingyu (Frontiers in Sustainable Food Systems, 2024)
Climate change is significantly and enduringly impacting global agricultural supply chains (ASCs), underscoring the urgent need to enhance their climate resilience. This study aims to identify key strategies for building agricultural supply chain resilience (ASCRes) in the context of climate change and their interrelationships. Through a comprehensive literature review and expert consultations, a framework of 12 strategies was developed. Using survey data from 312 Chinese ASC companies, BP-DEMATEL-ISM and PLS-SEM methods were employed to conduct causal analysis and factor level evaluation. The results indicate that “diversification of agricultural products and supply chain (SC) networks,” “Agriculture 4.0 and digital transformation,” and “taking proactive climate action” are critical strategies to enhance ASCRes in the context of climate change. These findings can provide theoretical basis for farmers, ASC companies, and governments to cope with the impact of climate change, so as to build more robust ASC systems.